Comprehensive Bibliometric Study on Cloud Accounting - Renita Janurika; Agus Munandar (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to conduct a comprehensive bibliometric analysis of cloud accounting research to map its development, identify influential publications, authors, and sources, and uncover key trends and emerging themes. Using data extracted from the Scopus database and analysed through bibliometric tools such as VOSviewer, the study examines publications spanning the period from 2012 to 2025. The results reveal three distinct research phases initial conceptualization, technology integration, and strategic adoption along with critical hotspots including data security, adoption by MSMEs, system interoperability, and regulatory compliance. Furthermore, recent literature highlights the convergence of cloud accounting with emerging technologies such as artificial intelligence and blockchain, signalling new research frontiers. This study sheds new light on the field of cloud accounting, particularly on its evolution and future research opportunities.